Palestine's Christians and the nationalist cause: the late Ottoman and mandatory periods - Freas, Erik (Routledge studies in Middle Eastern history, 2025)
"This book provides an historical overview of Palestine's Christian communities and their role in the Palestinian nationalist movement during the late Ottoman and British mandatory periods. More than being a history of Palestine's Christian Arabs, the book focuses on Palestine's Christians during the formative period of Palestinian Arab national identity, attentive to the broader topic of the relationship between nationalism and religion-in this case, between Arab identity and Islam. Whereas until recently historians have tended to assume that national and religious identities are distinct and mostly mutually exclusive things, more recent scholarship has addressed the fact that often there exists considerable overlap between the two, though it should be noted, often in ways that are not by any means inherently exclusive of those not belonging to the majority faith, as is the case here. The relationship is also an ever-changing one, hence the final chapter of the book, which functions as something of an epilogue regarding the current status of Palestine's Christians vis-à-vis their place in the nationalist cause and relationship with the broader Muslim population. The book will be of interest to historians and scholars focused on the modern Middle East, Palestinian history, Muslim-Christian inter-communal relations, and the relationship between nationalism and religion"--